Energy storage for frequency support in weak electrical grids - Jayamaha, Prasanthi Charmalee (2015)
INTEGRATING local renewable resources into the low voltage distribution system can create weak micro-grids with limited power capabilities and challenging control requirements. The low inertia in these micro-grids can result in significant frequency excursions when large load or generation changes are seen. Micro-grids may also be more susceptible to high harmonic distortion in their voltage due to non-negligible supply impedance. This calls for advance control techniques to regulate frequency and maintain voltage at the standards required of the utility grid. Failure to do so may incur disconnection of the weak grid from the main supply leading to cascading power disruptions to the consumers. This thesis explores one approach to improving the frequency control in weak grids in the presence of poor voltage quality by exploiting energy storage to independently and optimally dispatch active power to constrain frequency fluctuations within acceptable limits.